ANALISIS KONFLIK BATIN TOKOH MENTARI DALAM PICTORIAL BOOK “HARI INI ATAU BESOK” KARYA ASTRID SAVITRI - Anggreini Riana Pasaribu; Alpiani Tarigan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Inner conflict is a conflict experienced by humans with themselves or commonly referred to as an individual's internal problems. Conflict is something unpleasant that occurs or is experienced by story characters. If the character has the freedom to choose, he will not choose the events/conflicts that happen to him. This study aims to analyze the inner conflicts experienced by Mentari figures in the pictorial book “Hari Ini atau Esok” by Astrid Savitri. The analytical knife uses the theory of Kurt Lewin's approach. This research focuses on the inner conflicts experienced by Mentari characters in the pictorial book. The method used in this study is a qualitative descriptive method by collecting data in the form of written words which will then be followed by an analysis that has a connection with the context of the character's inner conflict. Data collection was carried out by reading and then paraphrasing sentences about the inner conflict of indecision experienced by Mentari figures in the Pictorial Book. The results of this study indicate that there is an inner conflict experienced by the main character named Mentari. Mentari figures in the process of his life he has gone through 3 forms of inner conflict, namely: 1.) Approach-approach conflict, 2.) Avoidance-avoidance conflict, 3.) Approachavoidance conflict ).